2019
DOI: 10.3390/nu11071478
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and Its Relation to Demographic, Socio-economic and Anthropometric Factors in Rural Primary School Children in Hai Phong City, Vietnam

Abstract: Little is known about the prevalence of anaemia and associated factors in school children in Vietnam. In this cross-sectional study, we aimed to determine the prevalence of anaemia and its subtypes, and the associations of types of anaemia with demographic, socio-economic and anthropometric factors among 6–9-year-old primary school children in rural areas of Hai Phong City, Vietnam. Haemoglobin (Hb) and mean corpuscular volume (MCV) were measured, and demographic, socio-economic and anthropometric data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
2
11
1
1
Order By: Relevance
“…Understanding factors correlated with anemia can provide more insight to the measures that can be applied to combat anemia. In the present study, we found that overweight and obese children were less likely to have anemia, which was consistent with a study conducted by Hoang [26], although other studies had detected both positive [27,28] and insignificant [29,30] correlations between anemia and BMI. Hoang et al [26] found that overweight/obese children may have had a higher hemoglobin concentration compared to normal weight or underweight children for some reasons that have not yet been explored.…”
Section: Discussionsupporting
confidence: 93%
“…Understanding factors correlated with anemia can provide more insight to the measures that can be applied to combat anemia. In the present study, we found that overweight and obese children were less likely to have anemia, which was consistent with a study conducted by Hoang [26], although other studies had detected both positive [27,28] and insignificant [29,30] correlations between anemia and BMI. Hoang et al [26] found that overweight/obese children may have had a higher hemoglobin concentration compared to normal weight or underweight children for some reasons that have not yet been explored.…”
Section: Discussionsupporting
confidence: 93%
“…This distribution of moderate to severe anaemia in our study could be because the University Teaching Hospital where the study was conducted is a level 3 referral hospital receiving patients whose conditions cannot be handled by lower levels of hospitals in the city. Furthermore, Zambia is a developing country where most households may not afford foods rich in iron and other minerals required for the formation of blood cells [26]. This study was conducted in an urban area and agreed with findings of some studies that found that children in such areas are more likely to be anaemic [27].…”
Section: Relationship Between Anaemia Types Severity and Age Groupssupporting
confidence: 86%
“…This 22-week parallel, double-blind, randomised, controlled trial was conducted from December 2016 to May 2017 in rural areas of Hai Phong City, Vietnam. Eight schools were selected for participation using a multistage sampling approach described in detail elsewhere 13 , 26 . Briefly, two of the eight rural districts in Hai Phong City were selected at random in the first stage, followed by the selection of four schools in each district among primary schools with student enrolment of ≥ 300.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the clustering induced by schools, the sample size was multiplied by a design effect of 1.42 [DE = 1 + ICC × (m − 1), where m = 8, the number of schools; and ICC = 0.06; the intracluster correlation coefficient]. The intracluster correlation coefficient was estimated from Hb data obtained during screening for eligibility 26 . Assuming 15% attrition rate, the target sample size for recruitment was 348 children [approximately 29 children in each strata defined by sex (boy/girl) and anthropometric status (undernourished/normal weight/overweight-obese)].…”
Section: Methodsmentioning
confidence: 99%